International Students’ Perceptions of Shelter-In-Place Notifications: Implications for University Officials - Johnson, Thomas C. (Journal of International Students, 2014)
Emergency notifications and shelter-in-place warnings on college and university campuses are generally issued in English and presuppose either a common shared language and culture or the adaptation of the warning system to a multilingual and multicultural social structure. This study examined the roles that language, culture, and emergency literacy played in international students’ perceptions of shelter-in-place notifications on a college campus. Students from Sweden, Bulgaria, and Kenya were recruited to participate in a focus group shortly after they had experienced shelterin-place warnings after an armed robbery occurred near their campus. These students were interviewed about their perceptions of emergency notification and shelter-in-place warnings. The study’s results suggest that, while an international student may be proficient in the English language, cultural issues, local practices and customs, and emergency illiteracy may hinder international students from understanding and appreciating the need to shelter-in-place or engage in self-protecting actions during a violent crime.